Nutrient Concentration, Water Brightness, Chlorophyll-a, and Phytoplankton Abundance as Indicators for Determining the Trophic Status of Lake Toba, North Sumatera - Indonesia - Saragih, Friska Setiawani; Djamil, Hasim; Juanda, Juanda; Mubarak, Ahmad Shofy; Hasan, Veryl; Sihombing, Agusmanto; Satyantini, Woro Hastuti (Department of Aquaculture, 2024)
The purpose of this study was to investigate the water quality and phytoplankton abundance in Lake Toba to determine its trophic status. This research was conducted from January to March 2024 at four stations in Lake Toba. Water samples were taken using a UWITEC water sampler and a plankton net and brought to the laboratory for analysis. The study measured physical and chemical water quality and phytoplankton abundance. The results showed a brightness ranging between 5.8 and 6.3 meters, chlorophyll-a content <10 µg/L, total nitrogen <750 µg/L, and phosphorus ranging from 20 µg/L to 30 µg/L. Based on these parameters, the nutrient quality of Lake Toba was classified as mesotrophic. Phytoplankton abundance ranged from 22,514 to 33,475 individuals/L, with 33 genera identified across nine classes: Bacillariophyceae, Chlorophyceae, Cyanophyceae, Coscinodiscophyceae, Dinophyceae, Euglenida, Fragilariophyceae, Mediophyceae, and Zygnemophyceae. The diversity index (H') was 2.631 - 2.723, the uniformity index (E) was 0.828 - 0.872, and the percentage of blue-green algae was 14.75 - 20.85. Zygnemophyceae was the most dominant phytoplankton class, with Staurastrum sp. being the most prevalent species. In conclusion, Lake Toba's waters are categorized as mesotrophic based on the chemical parameters and as eutrophic based on phytoplankton abundance, indicating potential nutrient enrichment issues that warrant further investigation.